Comparison of sea urchin and human mtDNA: evolutionary rearrangement. - Roberts, J W (1983)
Clones of full-length mtDNA have been isolated from a Strongylocentrotus franciscanus recombinant DNA library by screening a cDNA clone of cytochrome oxidase subunit 1 mRNA. Restriction fragment cross-hybridization analysis shows the following difference in gene arrangement between sea urchin and human mtDNA. The 16S rRNA and cytochrome oxidase subunit 1 genes are directly adjacent in sea urchin mtDNA. These two genes are separated in human and other mammalian mtDNAs by the region containing unidentified reading frames 1 and 2. In spite of the difference in gene order, gene polarity appears to have been conserved. We conclude that the difference in gene order reflects a rearrangement that took place in the sea urchin lineage since sea urchins and mammals last shared a common ancestor.